Meet: International Commission on Mathematical Instruction - Novotná, Jarmila (Scientia in educatione, 2020)
The article presents the International Commission on Mathematical Instruction (ICMI), a commission of the International Mathematical Union (IMU), an international non-governmental and non-profit-making scientific organisation whose purpose is to promote international cooperation in mathematics. It provides basic information about ICMI objectives, activities, cooperation with affiliated organisations and some new projects aiming to secure improvements in mathematics education.